In vitro evaluation of microfiltration degree of three temporary cements - Arrobo Espinosa, Paola (2018)
Objective: Evaluate the microfiltration degree of three temporary cements: IRM®, OBTUR ® and CAVIT® subjected to artificial aging. Methods: In 60 third molars, without caries, extracted because of therapeutic indication, cavities were made in the occlusal surface with pulp chamber opening of 4 mm x 4 mm, after irrigation with 2.5% NaClO and drying with cotton, the molars were randomly divided into three groups (n: 20) placing in each of them one of the three cements. The teeth were subjected to thermocycling at temperatures of -5, 37 and 55 ° C; during 900 continuous cycles, after which they were immersed in methylene blue for 24 hours, then sectioned and analyzed under a stereomicroscope to determine the microfiltration degree. Two fragments of each group were chosen randomly and prepared for scanning electron microscopy (SEM) observation. Results: The highest microfiltation degree was observed in IRM. CAVIT® and OBTUR® presented a similar degree of microfiltration with lower microfiltration, the observations made with the MEB corroborated these findings. Conclusions: The behavior of the provisional cements varies among them, IRM® presented a lower performance with higher filtration, there is no difference between CAVIT® and OBTUR® that presented better performance.